Anthocyanin-based pH-sensitive smart packaging films for monitoring food freshness - Lei Zhao; Yaqi Liu; Liang Zhao; Yong Wang (Journal of Agriculture and Food Research, 2022)
Anthocyanins are water-soluble natural pigments with good antioxidant and antibacterial properties, and their colors are pH sensitive to the environment. At present, the use of plant anthocyanins to prepare active and smart packaging film has attracted increasing attention in the field of food engineering. The use of anthocyanin-based pH-sensitive smart packaging films can not only effectively prolong the shelf life, but also monitor the freshness of food. This review mainly summarizes the mostly used packaging materials, preparation, structural and physicochemical properties, and the applications of anthocyanin-based films as pH-sensitive smart packaging for monitoring food freshness.